An AHP-based evaluation of car navigation apps in Korea - Chulmin Lim (International Telecommunications Society (ITS), 2018)
This study aimed to suggest the standards of evaluating car navigation app by examining and categorizing app's attributes. This study suggested four main criteria for app evaluation model; Functionality, Usability, Networking ability and Additional features and three sub-criteria belonging each main criterion. Also, the study conducted comparing each attribute and evaluating navigation apps competing in Korean market based on suggested criteria. As a result of this study, users put high weights on functionality, and the additional feature was least considered from users when they select car navigation app. Also, usability and networking ability show similar level of importance.
Keywords: 330; Car navigation app; AHP (Analytic Hierarchy Process); Korean car navigation market